1998
DOI: 10.1046/j.1365-2249.1998.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of synthetic linear epitope analogues of La/SSB for the detection of autoantibodies to La/SSB; specificity, sensitivity and comparison of methods

Abstract: In a previous study it was shown that La/SSB contains four linear epitopes, p147-154, p291-302, p301-318 and p349-364. The aim of the present study was to investigate the value of the synthetic epitope analogues of the La/SSB autoantigen for the detection of antibodies to La/SSB, in comparison with recombinant La and fragments of this protein. A total of 122 sera with anti-La/SSB activity, from patients with primary Sjögren's syndrome (pSS) or systemic lupus erythematosus (SLE), were tested in various peptide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 23 publications
(28 reference statements)
0
56
0
1
Order By: Relevance
“…The prevalence of antibodies against several La/SSB epitopes in Greek autoimmune sera is shown in table 2. In the same study it was also demonstrated that the most sensitive and specific peptide (amino acids 349-364) attached on a tetramer sequential oligopeptide SOC 4 has the same sensitivity for the detection of anti-La/SSB antibodies as the recombinant protein [49].…”
Section: Methods Of Detectionmentioning
confidence: 86%
“…The prevalence of antibodies against several La/SSB epitopes in Greek autoimmune sera is shown in table 2. In the same study it was also demonstrated that the most sensitive and specific peptide (amino acids 349-364) attached on a tetramer sequential oligopeptide SOC 4 has the same sensitivity for the detection of anti-La/SSB antibodies as the recombinant protein [49].…”
Section: Methods Of Detectionmentioning
confidence: 86%
“…Gel-based assays also depend on the precipitation of antigen-antibody complexes. The majority of anti-SS-B antibodies recognize linear rather than conformational epitopes (38). These occur at a low frequency in the SS-B ribonucleoprotein and have low antigenicity, resulting in a reduced ability to precipitate immune complexes.…”
Section: Practical Aspects Of Assay Performancementioning
confidence: 99%
“…The use of eucaryotic expression systems may help resolve this problem (24). Another potential source of pure antigen is synthetic peptides; however, these present solely linear epitopes and may therefore be useful only for antigens such as SS-B, where the major known epitopes are linear (38). The low specificity of ELISAs cannot be overcome simply by increasing the cutoff limits of detection.…”
Section: Practical Aspects Of Assay Performancementioning
confidence: 99%
“…In La, major epitopes have been identified in the RNP motif [56±59]. In particular, B-cell epitope mapping of the human La protein using the peptide mimotope scanning technique showed that anti-La autoantibodies from patients with SS and SLE recognize four major linear antigenic epitopes, spanning the amino acids sequences 145±164, 289±308, 301±318 and 349±364 [59,60]. A certain degree of similarity was observed between the segment 151± 158 of La and the RNP1 motif (Fig.…”
Section: Ro/la Epitopesmentioning
confidence: 99%